Automated targeting for property integration - Tan, Yin Ling (Animo Repository, 2021)
Resource conservation is an effective way for reducing operation cost and to maintain business sustainability. Most previous works have been restricted to "chemo-centric" or concentration-based systems where the characterisation of the streams and constraints on the process sinks are described in terms of the concentration of pollutants. However, there are many applications in which stream quality is characterised by physical or chemical properties rather than pollutant concentration. In this work, the automated targeting approach originally developed for the synthesis of composition-based resource conservation network is extended for property-based network. Based on the concept of insight-based targeting approach, the automated targeting technique is formulated as a linear programming (LP) model for which the global optimum is guaranteed. Two literature examples are solved to illustrate the proposed approach.